Poly[[chloridodimethanol(μ(3)-pyridine-2,3-dicarboxylato)europium(III)] methanol monosolvate] - Wu, Dayu (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, {[Eu(C(7)H(3)NO(4))Cl(CH(3)OH)(2)]·CH(3)OH}(n), contains one Eu(III) ion, one pyridine 2,3-dicarboxylate dianion (PDC), two CH(3)OH molecules coordinating to the metal atom, one coordinating chloride and one lattice occluded CH(3)OH molecule. In the crystal, each PDC anion coordinates to three adjacent Eu(III) ions by the pyridine N and O atoms of the carboxylate groups. The Eu(III) cation is eightfold coordinated by four carboxylate O atoms, one pyridine N atom, two MeOH and one chloride anion in the form of a distorted polyhedron. Extended coordination of the PDC ligand lead to the formation of a two-dimensional coordination polymer parallel to (10-1).